Poly (ADP-Ribose) Polymerase-1 (PARP1) Deficiency and Pharmacological Inhibition by Pirenzepine Protects From Cisplatin-Induced Ototoxicity Without Affecting Antitumor Efficacy - Tropitzsch, Anke; Müller, Marcus; Paquet-Durand, François; Mayer, Frank; Kopp, Hans-Georg; Schrattenholz, Andre; Müller, Andrea; Löwenheim, Hubert (Frontiers in Cellular Neuroscience, 2019)
Cisplatin remains an indispensable drug for the systemic treatment of many solid tumors. However, a major dose-limiting side-effect is ototoxicity. In some scenarios, such as treatment of germ cell tumors or adjuvant therapy of non-small cell lung cancer, cisplatin cannot be replaced without undue loss of efficacy. Inhibition of polyadenosine diphosphate-ribose polymerase-1 (PARP1), is presently being evaluated as a novel anti-neoplastic principle. Of note, cisplatin-induced PARP1 activation has been related to inner ear cell death. Thus, PARP1 inhibition may exert a protective effect on the inner ear without compromising the antitumor activity of cisplatin. Here, we evaluated PARP1 deficiency and PARP1 pharmacological inhibition as a means to protect the auditory hair cells from cisplatin-mediated ototoxicity. We demonstrate that cisplatin-induced loss of sensory hair cells in the organ of Corti is attenuated in PARP1-deficient cochleae. The PARP inhibitor pirenzepine and its metabolite LS-75 mimicked the protective effect observed in PARP1-deficient cochleae. Moreover, the cytotoxic potential of cisplatin was unchanged by PARP inhibition in two different cancer cell lines. Taken together, the results from our study suggest that the negative side-effects of cisplatin anti-cancer treatment could be alleviated by a PARP inhibition adjunctive therapy.